Inductive heating with a stepped diameter crucible. (5th June 2016) - Hadad, Yoav; Kochavi, Eytan; Levy, Avi
Graphical abstract: Stepped diameter crucible with SHC. On the right, a section of the SHC is shown with current flow. Highlights: We present a novel solution for vacuum inductive heating of a gradual crucible. A numerical model was built to estimate the temperature gradient in the crucible. The method was validated with an experimental inductive furnace setup. The solution was shown enable to use in gradual diameter crucible. Abstract: Induced heating in a vacuum environment is the most common method for high precision and purity casting. A significant disadvantage in this process is that it is designed for heating in a crucible of uniform diameter. However, it is not suited for the heating of a crucible with stepped diameter. The use of a variable diameter crucible enables to place a larger amount of raw material into the wider diameter section of the crucible. After the material melts, the liquid fills the narrow part of the crucible and enables better control of liquid flow into the casting mold. Hence, in this research we present a novel solution for vacuum inductive heating in a stepped diameter crucible by using a secondary heating coil (SHC). In order to examine the SHC solution, numerical models were developed to describe the temperature distribution and the heat generation in the crucible. Experiments on a vacuum induction furnace were conducted to validate the numerical models of the SHC. A good match was acquired between the numerical and experimental results. The results of the simulations and experiments have shown great improvement in the capability of heating a stepped diameter crucible with an SHC.